Distribuição espacial de atributos florestais em um ecossistema de Mecrusse, no sul de Moçambique (Revista Espinhaço, 2022)
Spatial variability of biometric variables can assist in planning and stratification of forest inventories. is work aimed to check the dependence of spatial distribution in a fragment of Mecrusse, Androstachys johnsonii, by comparing the spatial distribution of dominant height, volume, basal area, and density of (a) all species, (b) the dominant species and (c) all species excluding the dominant. Were used data from 79 temporary plots of 0.2 ha in the region of, Gaza Province, southern Mozambique. Were measured all the trees with diameter at breast height (DBH), greater than or equal to 10 cm (DBH ≥ 10 cm). e variables were associated with the geographic coordinate of the collection point for the processing of data by geostatistics techniques. Have been tested three models (Spherical, Exponential and Gaussian), by the method of ordinary least squares. e exponential model obtained best fit between the others and was selected and used to estimate the variables for all forests. e variable dominant height showed no spatial dependence, when analyzed for all forest or to the species of Androstachys johnsonii. e dominance of the species studied presented spatial dependence. e interpolation by ordinary kriging spatial distribution showed basal area ranging from 4 to 42 m2ha-1, and North and northeast regions with higher concentrations than the South.
Keywords: Androstachys johnsonii; monodominance; geostatistics; kriging